Penerapan Hukum Pidana Terhadap Pungutan Liar Oleh Preman Di Jembatan Tuntungan Pancur Batu (Studi Di Polsek Pancur Batu) - Imanuel Widantara Pandia; Rizkan Zulyadi; Wessy Trisna (Universitas Medan Area, 2023)
Extortion activities played by thugs are very disturbing to the community. The act of thuggery that occurred on the Tuntungan bridge which connects the Durin Jangak Village area, Pancur Batu District, the criminal act of extortion that occurred against residents who crossed the bridge. As a result, actions like this often lead to chaos and violence between the community and these individuals. The purpose of this research is to find out how the laws governing illegal levies committed by thugs in Pancur Batu and how the Pancur Batu police are trying to deal with illegal levies. The research method used in this research is normative juridical, namely a research method that examines document studies, namely by using various data such as legislation, court decisions as well as primary, secondary and tertiary materials. The results of the study show that the role of the Indonesian National Police as Law Enforcement and Protector, Protector, and Public Servant demands a professional handling of thuggery, by taking firm action against the perpetrators of thuggery and taking concrete steps to overcome thuggery and providing suggestions and reviewing public policies. so that it can be more targeted, so that the handling of thuggery does not continue to grow and increase in number, especially with regard to acts of thuggery committed by individuals, groups, groups, and mass organizations, which result in conflicts between ethnic groups and groups and have the potential to divide the nation.